THE INFLUENCE OF INTERACTIVE LEARNING MEDIA, ANIMATED VIDEOS, ON STUDENTS’ LEARNING INTERENST IN WATER CYCLE MATERIAL FOR CLASS V SD NEGERI 32 PALEMBANG - Yoda, Fitri; Sukardi; Mega Kusuma Putri (Cerdas Proklamator, 2024)
This research aims to determine the effect of animated video interactive learning media on students' learning interest in the water cycle material for class V SD Negeri 32 Palembang. The research method used isquantitative experimentation with the design of the Posttest-Only Control Design research design. Thepopulation of this research was all fifth grade students at SD Negeri 32 Palembangwith a total of 46students. The sample for this research was class V.A as the experimental class and Class V.B as the control class, where class V.A was 22 students and class V.B was 25 students with the technique used was saturated sampling technique. The data collection techniques used are questionnaires, observation and documentation. The data analysis technique used was the t-test (Independent Sample T-Test). From the results of processingresearch data using the SPSS 26 application, the value of tcount = 4.333 and the value of ttable = 1.680 with ? = 0.05 and df = 44, thus tcount = 4.333 > ttable = 1.680. Accordingto the hypothesis testing criteria, it can be concluded that Ho is rejected and Ha is accepted or that there is an influence of interactive learningmedia, animated videos, on students' learning interest in the class V water cycle material at SD Negeri 32Palembang.Keywords: Animation Video Interactive Media, Interest in Learning